EARLY PREVENTION OF OCCLUSAL DISORDERS OF DENTAL ARCHES - Oleksyn, K.Z.; Paliichuk, I.V. (World of Medicine and Biology, 2021)
Dental caries is one of the main factors of occlusal disorders, that changes location of occlusal contact points and is the cause of atypical mandibular movements, occlusal overloading and trauma. The objective of the research was to carry out early prevention of occlusal disorders in patients with carious lesions using modern restorative methods in order to prevent occlusal disorders using the methods of restorations of the affected chewing surfaces considering functional anatomy and subsequent checking of occlusal relationships with the help of the T-Scan Novus occlusal analysis system. Ninety students living in the regions with low fluoride level were examined. The treatment was carried out by the methods of direct and indirect restorations. The paper contains the results of redistribution of occlusal contacts in carious lesions and restoration of the first molar without considering the principles of functional anatomy, and the results immediately and 6 months after restorations of the chewing surfaces of the first molars considering the occlusal determinants.